The degree of p70 S6k and S6 phosphorylation in human skeletal muscle in response to resistance exercise depends on the training volume. - Terzis, Gerasimos; Spengos, Konstantinos; Mascher, Henrik; Georgiadis, Giorgos; Manta, Panagiota; Blomstrand, Eva (Eur J Appl Physiol, 2010)
Regular performance of resistance exercise induces an increase in skeletal muscle mass, however, the molecular mechanisms underlying this effect are not yet fully understood. The purpose of the present investigation was to examine acute changes in molecular signalling in response to resistance exercise involving different training volumes. Eight untrained male subjects carried out one, three and five sets of 6 repetition maximum (RM) in leg press exercise in a random order. Muscle biopsies were taken from the vastus lateralis both prior to and 30 min after each training session and the effect on protein signalling was studied. Phosphorylation of Akt was not altered significantly after any of the training protocols, whereas that of the mammalian target of rapamycin was enhanced to a similar extent by training at all three volumes. The phosphorylation of p70S6 kinase (p70(S6k)) was elevated threefold after 3 × 6 RM and sixfold after 5 × 6 RM, while the phosphorylation of S6 was increased 30- and 55-fold following the 3 × 6 RM and 5 × 6 RM exercises, respectively. Moreover, the level of the phosphorylated form of the gamma isoform of p38 MAPK was enhanced three to fourfold following each of the three protocols, whereas phosphorylation of ERK1/2 was unchanged 30 min following exercise. These findings indicate that when exercise is performed in a fasted state, the increase in phosphorylation of signalling molecules such as p70(S6k) and the S6 ribosomal protein in human muscle depends on the exercise volume.
Keywords: Biopsy; Exercise; Fasting; Humans; Hypertrophy; Male; Muscle, Skeletal; Phosphorylation; Resistance Training; Ribosomal Protein S6; Ribosomal Protein S6 Kinases, 70-kDa; signal transduction; Young Adult